Variable “subject” presence in Australian Sign Language and New Zealand Sign Language - McKee, Rachel; Schembri, Adam; McKee, David; Johnston, Trevor (Language variation and change, 2011)
This article reports the findings of parallel studies of variable subject presence in two closely related sign language varieties, Australian Sign Language (Auslan) and New Zealand Sign Language (NZSL). The studies expand upon research in American Sign Language (ASL) (Wulf, Dudis, Bayley, & Lucas, 2002) that found subject pronouns with noninflecting verbs to be more frequently unexpressed than expressed. The ASL study reported that null subject use correlates with both social and linguistic factors, the strongest of which is referential congruence with an antecedent in a preceding clause. Findings from the Auslan and NZSL studies also indicated that chains of reference play a stronger role in subject presence than either morphological factors (e.g., verb type), or social factors of age, gender, ethnicity, and language background. Overall results are consistent with the view that this feature of syntactic variation may be better accounted for in terms of information structure than sociolinguistic effects.